ANALISIS IMPLEMENTASI PRINSIP SUSTAINABLE LIVING PADA PERUSAHAAN IKEA - Vina Maulidah Chusnia (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
Sustainability shows that the organization has the attitude to be able to contribute in maintaining and developing sustainable development. In its development, sustainable living can be applied through the concept of effective and efficient work, for example by applying the supply value with a sustainable concept. IKEA has become a company that has approved the ten principles of sustainable development by the UN Global Compact, making it one of the most successful companies in adopting the concept of sustainability. This study aims to find out how to implement the sustainability principle, which has 4 supporting aspects, namely risk management, transparency, strategy and culture of IKEA company through sustainable Supply Chain Management to realize Good Corporate Governance. This study uses a qualitative approach with data collection using library research and literature study to produce descriptive data. In this article, the authors find the fact that there has been alignment between IKEA's commitment to the 10 principles of sustainable development with their sustainable living report in 2021. The results show that IKEA has successfully implemented the sustainability principle which consists of 4 supporting aspects that are considered to be able to generate competitive advantage. IKEA's success in implementing sustainability principles can make it a role model for the organization towards positive change.